The Walking Dead: The Anthropocene as a Ruined Earth. (3rd July 2017) - Beuret, Nicholas; Brown, Gareth
Abstract : Much has been made of the claim that humanity has ascended to the status of a terrestrial force and inaugurated a new geological epoch, the Anthropocene. While attention has been paid to the contestable nature of the epoch and its disputed histories, insufficient attention has been paid to the significance of the Anthropocene for political praxis. Contrary to much Anthropocenic discourse that articulates a renewed sense of mastery over nature through assertions of humanity's complete subsumption of the environment, recent work in both science and technology studies and human geography suggests an alternate reading of the Anthropocene as an epoch without mastery, one where humanity exists in a permanent state of vulnerability. The political significance of this state of vulnerability is explored through a reading of popular TV show The Walking Dead, a post-collapse narrative of a world in ruins and overrun by zombies. On a ruined earth, political praxis is orientated not towards a return of the earth to its previous productive state, but rather as an unending labour of survival and salvage. Survival is not a life reduced to bare life, but rather a state of tension between a life reduced to necessity, and the refusal to separate the question of how to live from the work of securing life itself. Left unresolved, this tension animates the politics of the Anthropocene, suggesting that in place of the teleology of progress social life is organised within it through unceasing care and repair time.